MENINGKATKAN MOTIVASI DAN AKTIVITAS BELAJAR SISWA DI KELAS VII.C MTsN PANINJAUAN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Yusnidar, Yusnidar (STKIP PGRI Sumatera Barat, 2018)
AbstractGood motivation is a key for success. Equipped with good classroom activities, it will be easy for students to increase their result. In grade VII MTsN Paninjauan, Some student have got good result in study, except for students in VII.c. To increase their result, we have to increase their motivation and classroom activities. All of this effort, we do in a series of activities in classroom action research that we do in two cycle activities. Base on first observation, the model that suitable for student is cooperative learning type Jigsaw. As the result, we find that student motivation and classroom are increase. It is also followed by increasing of their study result